Determinants and impact of alexithymia on quality of life in Parkinson's disease - Alvarado-Bolaños, A.; Cervantes-Arriaga, A.; Zuazua-Vidal, L.; Esquivel-Zapata, Ó.; Alcocer-Salas, Á.; Rodríguez-Violante, M. (Neurología (Barcelona, English ed. ), 2023)
Alexithymia is a neuropsychiatric symptom conceptualized as difficulty identifying and describing feelings. Although associated with other non-motor symptoms, mainly neuropsychiatric, alexithymia may present as an isolated symptom in persons with Parkinson's Disease (PwP). The objective of the study is to identify determinants of alexithymia and its association with quality of life (QoL) in Parkinson's disease. Subjects with Parkinson's disease were recruited. The following instruments were applied: Movement Disorders Society Unified Parkinson's Disease Rating Scale (MDS-UPDRS), Non-Motor Symptoms Scale (NMSS), Montreal Cognitive Assessment (MoCA), Toronto alexithymia scale (TAS-20) and Parkinson's Disease Questionnaire (PDQ-8). Matched healthy controls were screened using TAS-20. Clinical and demographical variables were compared between alexithymic and non-alexithymic. Regression models were used to find determinants of alexithymia. Impact of alexithymia on QoL was estimated with a linear regression model. 98 patients were included. 56.1% PwP and 28.8% controls were alexithymic (p<0.001). Education level (OR 0.86) and NMSS urinary score (OR 1.09) determined alexithymia as well as TAS-20 score. Alexithymia was an independent determinant of QoL. Alexithymia is a prevalent independent non-motor symptom in PwP with impact on QoL. Low education level and urinary symptoms are important determinants of alexithymia. La alexitimia es un rasgo neuropsiquiátrico conceptualizado como la dificultad para identificar y describir sentimientos. Aunque está asociado con otros síntomas no motores, principalmente neuropsiquiátricos, sigue siendo una característica independiente de las personas con enfermedad de Parkinson (PcP). El objetivo del estudio es identificar los determinantes de la alexitimia y su asociación con la calidad de vida en la enfermedad de Parkinson. Se reclutaron sujetos con enfermedad de Parkinson. Se aplicaron los siguientes instrumentos: escala unificada de la enfermedad de Parkinson de la Sociedad de Trastornos del Movimiento (MDS-UPDRS), escala de síntomas no motores (NMSS), evaluación cognitiva de Montreal (MoCA), escala de alexitimia de Toronto (TAS-20) y cuestionario de la enfermedad de Parkinson (PDQ-8). Se incluyeron controles sanos pareados, los cuales se evaluaron usando la TAS-20. Las variables clínicas y demográficas se compararon entre pacientes alexitímicos y no alexitímicos. Se utilizaron modelos de regresión para estimar los predictores de alexitimia. El impacto de este rasgo neuropsiquiátrico en la calidad de vida se estimó con un modelo de regresión lineal. Se incluyeron 98 pacientes. El 56,1% de PcP y el 28,8% de los controles fueron alexitímicos (p < 0,001). El nivel educativo (OR 0,86) y la puntuación urinaria del NMSS (OR 1,09) determinaron la alexitimia, así como la puntuación del TAS-20. La alexitimia fue un determinante independiente de calidad de vida. La alexitimia es un síntoma independiente no motor prevalente con impacto en la calidad de vida. El bajo nivel educativo y los síntomas urinarios son determinantes importantes de esta condición.